Tax Reform Trends in OECD Countries - Brys, Bert (OECD Taxation Working Papers, 2011)
Over the last two decades almost all OECD countries have made major structural changes to their tax systems. In the case of the personal and corporate income tax regimes reforms have generally been rate reducing and base broadening, following the lead given by the United Kingdom in 1984 and the United States in 1986. In some countries, including Australia and New Zealand, reforms have been profound and sometimes implemented over a very short period of time. In others, including most of Europe, Japan and many other Asian countries, reform has been a gradual process of adaptation